Fenomena Relawan Politik dalam Kontestasi Presidensial 2014 - Bambang Arianto (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This article describes how the presidential contestation in 2014 was characterized by the presence of political volunteers. Here political volunteers is deﬁ ned as a manifestation of strengthening active participation of citizens in promoting substantive democracy. This article argues that the rise of a new social movement has brought a tradition of voluntarism in politics. In addition he voluntarism has transformed the values of patrimonial political and oligarchy onto active popular voluntarism and participatory. The political volunteers who employed oﬄ ine and online medium have clearly increased public participation in Indonesia.This article has also argued the presence of political volunteers has positively contributed to developtment  of extra parlementary democracy model.